(untitled) (CIPEEX, 2026)
This summary analyzes the effectiveness of accessibility and inclusion guarantees promoted by the Court of Justice of the State of Goiás (TJGO) in serving people with hearing impairments, especially the deaf population. The research is based on the observation that, despite regulatory advances in Brazil, such as the Brazilian Inclusion Law (Law No. 13,146/2015) and Resolution No. 401/2021 of the National Council of Justice, access to justice by the deaf community still faces significant barriers, especially in terms of communication. The main objective is to verify whether the actions taken by the TJGO have been effective in promoting the full inclusion of these individuals. A qualitative and descriptive approach was adopted, based on bibliographic research, document analysis, and institutional data collection, with an emphasis on official reports, institutional emails, specific legislation, and internal regulations. The results show significant advances, such as the training of civil servants in Libras, the presence of interpreters at hearings, and the adaptation of electronic systems. However, structural gaps persist, such as the lack of an institutionalized Libras Center, the limited number of qualified professionals, and the absence of specific policies for deaf people who are not fluent in Libras. It is concluded that, although the TJGO is formally committed to the constitutional principles of dignity, equality, and broad access to justice, there is still a need for institutional improvement. The Goiás judiciary needs to invest in broader, more technological, and more sensitive inclusive solutions for the communication diversity of the deaf community in order to ensure truly accessible, continuous, and dignified service.